Comparison of efficacy of intra-lesional injections of platelet rich plasma therapy versus intralesional triamcinolone acetonide in the treatment of patients with alopecia areata at a tertiary care hospital - Altaf Hussain; Syed Ahmed Ali Gardezi; Ilyas, Saima; Sultan, Nadia; Shahbaz Aman (Journal of Pakistan Association of Dermatologists, 2023)
Objective Alopecia areata (AA) is a prevalent autoimmune disorder characterized by hair loss triggered by inflammation. Platelet-rich plasma (PRP) has recently gained attention as a novel dermatological treatment, with initial findings indicating its potential benefits in promoting hair growth. Â Objective The aim of this study is to evaluate and compare the effectiveness of intralesional injections of platelet-rich plasma therapy with local injections of Triamcinolone acetonide in managing alopecia areata patients. Â Methods It is a randomized controlled trial done at Dermatology Department, Mayo Hospital, Lahore from July, 2022 to January, 2023. Group A received intralesional injections of PRP. Group B received intralesional injections of triamcinolone acetonide (10 mg/ml). The two modalities of treatment were given at 0, 4 and 8 weeks and response was assessed after 1 month of completion of treatment The treatment response was assessed using the Severity of Alopecia Tool (SALT) score, after 12 weeks of therapy. The hair regrowth more than 50% from baseline was considered as efficacious. Â Results Of these 108 study cases, 41 (38.0 %) were male patients while 67 (62.0 %) were female patients. Mean age of our study cases was 31.28 Â± 11.55 years. Mean disease duration was 11.31Â±7.34 months and 70 (64.8 %) had duration of illness more than 6 months. Efficacy was noted in 45 (41.7%), in group A efficacy was noted in 29 (64%) versus 16 (36%) in group B (P=0.011). Â Conclusion The present study revealed that platelet rich plasma injections are effective and safe in patients with alopecia areata compared to Triamcinolone acetonide. Efficacy was higher among patients treated with intraâ€“ lesional injections of platelet rich plasma in comparison with Triamcinolone acetonide but not significant as p value (P=0.011). Â